Nuclear PI3K signaling in cell growth and tumorigenesis - Davis, William J.; Lehmann, Peter Z.; Li, Weimin (Frontiers in Cell and Developmental Biology, 2015)
The PI3K/Akt signaling pathway is a major driving force in a variety of cellular functions. Dysregulation of this pathway has been implicated in many human diseases including cancer. While the activity of the cytoplasmic PI3K/Akt pathway has been extensively studied, the functions of these molecules and their effector proteins within the nucleus are poorly understood. Harboring key cellular processes such as DNA replication and repair as well as nascent messenger RNA transcription, the nucleus provides a unique compartmental environment for protein-protein and protein-DNA/RNA interactions required for cell survival, growth, and proliferation. Here we summarize recent advances made towards elucidating the nuclear PI3K/Akt signaling cascade and its key components within the nucleus as they pertain to cell growth and tumorigenesis. This review covers the spatial and temporal localization of the major nuclear kinases having PI3K activities and the counteracting phosphatases as well as the role of nuclear PI3K/Akt signaling in mRNA processing and exportation, DNA replication and repair, ribosome biogenesis, cell survival, and tumorigenesis.